General principles of property laws in Malaysia - Mohamad, Nor Asiah; Bisa, Naser (Yetkin Yayinlari, 2020)
This paper describes the various types of laws dealing with property in Malaysia. The discussion focuses on the general principles relating to real estate law as well as some areas of Muslim law including waqf and unclaimed estates. The investigation is note-worthy taking into account the colourful background of the Malaysian socio-legal structures. Whatever the law applicable, it is not simply a piece of manual but a legal document meant to uphold justice and fairness in the society, having three major ethnics with different languages, religions and customs. Property symbolises dignity, power and the strength of the people, thus competition is predictable. This paper discusses factors that contribute to various backgrounds of Malaysian property laws as well as the current administration of the property. A correct understanding of the Malaysian legal system as well as the sources of law are crucial to appreciate the issues and promote justice related to general property law as well as Muslim law.Under the title General Principles of Property law in Malaysia, this paper maps the legal framework of real property, which stands on a strong basis of civil and Shariah law. The paper concludes that the general principles of property laws that are rooted in the socio-legal history and moving forward in tandem with the contemporary needs and expectation of the people. In so doing, the law must be flexible, contemporary and viable.